Detecting foreign bodies in food - Edwards, M. (Woodhead Publishing, 2011)
Foreign bodies are the biggest single source of customer complaints for many food manufacturers, retailers, and enforcement authorities. Foreign bodies are any undesirable solid objects in food and range from items entirely unconnected with the food, such as glass or metal fragments, to those related to the food, for example bones or fruit stalks. Detecting Foreign Bodies in Food discusses ways of preventing and managing foreign body incidents, and reviews the range of both current and emerging methods and technologies available for detection and control.